Development and User Experience Evaluation of an Experience Sampling-Based Dietary Assessment Method - Joke Verbeke; Christophe Matthys (Current Developments in Nutrition)
Background: Most technology-based dietary assessment methods use the same methodology as traditional dietary assessment methods resulting in similar limitations and biases. Experience sampling methodology (ESM) is a real-life real-time data-capturing method that is explored as an alternative methodology for dietary assessment to improve feasibility and data accuracy. Objectives: This research aimed to develop and evaluate an experience sampling-based dietary assessment method (ESDAM) measuring habitual dietary intake. Methods: Starting from a food frequency questionnaire, experience sampling principles were implemented resulting in a pilot ESDAM. Second, the pilot ESDAM was evaluated for feasibility and convergent validity compared with a 3-d food record. Mean intake with standard deviations was compared between the pilot ESDAM, food record (FR), and food frequency questionnaire (FFQ), and Spearman correlation coefficients (SCCs) were calculated. Third, following a literature review and expert opinion, the questions and design of the pilot ESDAM were further adapted to ESM and implemented in an experience sampling survey application. The resulting prototype ESDAM underwent 2 rounds of user experience (UX) evaluation in which 10 persons tested ESDAM for 1 wk followed by a structured evaluation interview. Results: The pilot ESDAM, FR, and FFQ were completed by 27 participants and the evaluation questionnaire by 78 participants. Mean energy intake by the FFQ, pilot ESDAM, and FR was 1272.2 ± 308.9 kcal/d, 1592.3 ± 358.9 kcal/d, and 1664.6 ± 257.8 kcal, respectively. The evaluation revealed the limited time window (19:00–23:00) to respond was inconvenient, good acceptability, and ease of use of the pilot ESDAM. The UX evaluation study revealed overall good acceptability, ease of use, and low burden of the different prototypes of ESDAM. Conclusions: ESM could advance the field beyond traditional methodologies and improve feasibility. ESDAM is unique in assessing dietary intake quantitatively through ESM. Additional assessment of validity might shed light on the data accuracy of ESDAM.